2022
DOI: 10.29169/1927-5129.2022.18.10
|View full text |Cite
|
Sign up to set email alerts
|

Earth’s Temperature: The Effect of the Sun, Water Vapor, and CO2

Abstract: The purpose of this study is to show the Sun controls the Earth’s temperature daily and over decades and millennia. A secondary objective is to show CO2 contributes to the warming of the Earth through increased enthalpy (heat content). The methodology is to record temperature and relative humidity at many weather stations around the globe to provide a picture of the constantly changing atmosphere over twelve months. Daily measurements of the molecular fraction of CO2 are converted to weight to calculate the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A paper, "Earth's Temperature: The Effect of the Sun, Water Vapor, and CO 2 ", published in November 2022 and subsequently revised, showed that temperature warming by CO 2 is too small to measure [2]. This paper builds on both documents and uses a data set of 240 empirical values from 20 locations.…”
Section: Introductionmentioning
confidence: 99%
“…A paper, "Earth's Temperature: The Effect of the Sun, Water Vapor, and CO 2 ", published in November 2022 and subsequently revised, showed that temperature warming by CO 2 is too small to measure [2]. This paper builds on both documents and uses a data set of 240 empirical values from 20 locations.…”
Section: Introductionmentioning
confidence: 99%